High Intensity Transplanting Increases Yield in Indigenous Aromatic Rice, Tulaipanji- a Case Study - Sen, Dhiman; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2010)
Tulaipanji is indigenous aromatic rice adapted in a small pocket of West Bengal, India. It is popular for its medium-long slender grain with high amylose content and strong aroma even after parboiling. Farmers traditionally grow this cultivar in poor fertile soil under late sown and moisture stress condition to produce best quality harvest. However, such stress factors are responsible for low average yield. The modified transplanting technique, High Intensity Transplanting can increase average productivity even after maintaining traditionally followed stress conditions to produce quality aromatic grain of tulaipanji.